Utilization and outcomes of extracorporeal CO2 removal (ECCO2R): Systematic review and meta‐analysis of arterio‐venous and veno‐venous ECCO2R approaches. Issue 5 (12th December 2021) - Yu, Tiffany Z.; Tatum, Robert T.; Saxena, Abhiraj; Ahmad, Danial; Yost, Colin C.; Maynes, Elizabeth J.; O'Malley, Thomas J.; Massey, Howard T.; Swol, Justyna; Whitson, Bryan A.; Tchantchaleishvili, Vakhtang
Abstract: Introduction: Extracorporeal carbon dioxide removal (ECCO2 R) provides respiratory support to patients suffering from hypercapnic respiratory failure by utilizing an extracorporeal shunt and gas exchange membrane to remove CO2 from either the venous (VV‐ECCO2 R) or arterial (AV‐ECCO2 R) system before return into the venous site. AV‐ECCO2 R relies on the patient's native cardiac function to generate pressures needed to deliver blood through the extracorporeal circuit. VV‐ECCO2 R utilizes a mechanical pump and can be used to treat patients with inadequate native cardiac function. We sought to evaluate the existing evidence comparing the subgroups of patients supported on VV and AV‐ECCO2 R devices. Methods: A literature search was performed to identify all relevant studies published between 2000 and 2019. Demographic information, medical indications, perioperative variables, and clinical outcomes were extracted for systematic review and meta‐analysis. Results: Twenty‐five studies including 826 patients were reviewed. 60% of patients (497/826) were supported on VV‐ECCO2 R. The most frequent indications were acute respiratory distress syndrome (ARDS) [69%, (95%CI: 53%–82%)] and chronic obstructive pulmonary disease (COPD) [49%, (95%CI: 37%–60%)]. ICU length of stay was significantly shorter in patients supported on VV‐ECCO2 R compared to AV‐ECCO2 R [15 (95%CI: 7–23) vs. 42 (95%CI: 17–67) days, p  = 0.05]. In‐hospital mortality was not significantly different [27% (95%CI: 18%–38%) vs. 36% (95%CI: 24%–51%), p  = 0.26]. Conclusion: Both VV and AV‐ECCO2 R provided clinically meaningful CO2 removal with comparable mortality. Abstract : CO2 removal can be meaningfully achieved via extracorporeal devices (VV‐ECCO2 R and AV‐ECCO2 R) in patients suffering from hypercapnic respiratory failure without any difference in mortality between the devices.